Insufficiency of urinary acid excretion of overweight or obese patients with chronic kidney disease and its involvement with renal tubular injury. Issue 11 (1st May 2019) - Eguchi, Koji; Izumi, Yuichiro; Nakayama, Yushi; Inoue, Hideki; Marume, Takahiro; Matsuo, Naomi; Hiramatsu, Akiko; Ono, Makoto; Kakizoe, Yutaka; Kuwabara, Takashige; Nonoguchi, Hiroshi; Mukoyama, Masashi
ABSTRACT: Aim: Metabolic acidosis occurs due to insufficient urinary ammonium excretion as chronic kidney disease (CKD) advances. Because obese subjects tend to have excessive consumption of protein and sodium chloride, they are prone to chronic acid loading and may therefore be predisposed to acid‐induced kidney injury. We investigated the involvement of obesity in ammoniagenesis within damaged kidneys. Methods: In the clinical study, urinary ammonium excretion was compared between 13 normal‐weight and 15 overweight/obese CKD outpatients whose creatinine clearance was higher than 25 mL/min. For animal experiments, NH4 Cl was loaded to KKAy/TaJcl (KKAy), a metabolic syndrome model, and control BALB/c mice for 20 weeks. Kidney injury was evaluated through histological analysis and the expression of proinflammatory markers. Results: Urinary ammonium excretion was lower in overweight/obese patients than in normal‐weight patients, while intakes of protein and sodium chloride were higher in overweight/obese patients, implying that subclinical metabolic acidosis occurs in overweight/obese patients. The increase in urinary ammonium excretion induced by NH4 Cl loading was attenuated in KKAy mice after 16 weeks, whereas the increase was maintained in BALB/c mice throughout the study period. Histological study and real‐time polymerase chain reaction analysis showed proximal tubular injury and enhanced expression levels of neutrophil gelatinase‐associated lipocalin (NGAL) protein and messenger RNA, respectively, in KKAy mice but not in BALB/c mice. Finally, urinary NGAL concentration was higher in overweight/obese patients than in normal‐weight patients in the early stage of CKD. Conclusion: Obesity could facilitate the induction of subclinical metabolic acidosis and acid accumulation in the kidney, which may potentially exacerbate kidney injury in CKD patients. SUMMARY AT A GLANCE: This study investigated the involvement of obesity in ammoniagenesis within damaged kidneys and found that obesity could facilitate the induction of subclinical metabolic acidosis and acid accumulation in the kidney.